Methimazole as a rare cause of hepatitis in childhood: a case report - Íris Santos-Silva; Catarina Chaves; Sandra Ferreira; Isabel Gonçalves; Alice Mirante; Vânia Benido-Silva (Publicaciones Permanyer, 2024)
Hyperthyroidism is an endocrine disorder whose treatment of choice is methimazole, due to the low risk of adverse reactions. Drug-induced liver injury by methimazole is rare, especially in pediatric age, but when it occurs it is potentially serious. We present a case report of drug-induced liver injury due to methimazole in a 12-year-old boy diagnosed with hyperthyroidism due to Graves' disease. The patient had signs and symptoms of thyrotoxicosis, but not clinical findings related to the liver condition. After the discontinuation of treatment and ablative therapy with Iodine131, there was an excellent clinical and analytical evolution, with recovery of cytocholestasis to almost normal values. Thus, early recognition of this serious adverse effect through frequent monitoring of liver enzymes along with thyroid function is essential to avoid unfavorable outcomes.